Health and social policies to advance Brazil’s End TB agenda during and after COVID-19: An analysis from tripartite governance and normative innovation perspectives - Natacha Martins Ribeiro; Mônica Cristina Ribeiro Alexandre d’Auria de Lima; Aline Aparecida Monroe; André Luiz Teixeira Vinci; Beatriz Fornaziero Vigato; Rebeca Sousa Braga; Melisane Regina Lima Ferreira; Valter Chicalo António Caripa; Rander Junior Rosa; Nathalia Zini; Heriederson Sávio Dias Moura; Willie Otávio Bueno Bernardi; et al. (PLoS ONE, 2026)
Objectives To critically analyze, through a systematic documentary approach, the health and social policies implemented in Brazil to address tuberculosis during and after the COVID-19 pandemic, identifying advances, challenges, and gaps in federal coordination. Methods Qualitative documentary study of 438 normative documents published between 2020 and 2024, including laws, decrees, ordinances, and resolutions at the federal, state, and municipal levels. Thematic content analysis was applied to examine the empirical material. Results Six thematic categories emerged: financial aspects and resources; management and policies; social support; social context and community participation; development and innovation; and health care strategies. The analysis revealed lack of coordination among governmental spheres, regional inequalities, and gaps in innovation and management. Conclusion Addressing TB in the post-pandemic context requires federal integration, strengthened evidence-based policies, and investments in innovation, offering relevant lessons for countries with similar socioeconomic contexts.